El juego de mesa y los lenguajes artísticos como herramientas para la educación emocional = Abweichender Titel: Board Games and Artistic Languages as Pedagogical Tools for Emotional Education - Sánchez-Carralero, Noemí (Cauriensia, 2025)
Board games, beyond their recreational purpose, enable the simulation of social situations, the resolution of conflicts, and the practice of communication skills within a safe and collaborative environment. Artistic languages offer expressive pathways through which children can channel emotions, stimulate creativity, and strengthen self-esteem. This study presents an educational innovation experience carried out with prospective Early Childhood Education teachers, aimed at enriching their pedagogical practices and fostering the holistic development of young learners. Through a Project-Based Learning (PBL) approach, a board game was designed and implemented to address emotional learning and content from the area of Knowledge of the Natural, Social, and Cultural Environment, integrating music, visual arts, and movement. The article describes the game-design process, its basic rules and dynamics, and its implementation in an Early Childhood classroom with five-year-old pupils. Drawing on qualitative observations and the assessments of both the classroom teacher and the participating university students, the analysis highlights the potential of the experience, revealing benefits in motivation, social interaction, and the development of emotional and social competences